Colon 26 Adenocarcinoma (C26)-Induced Cancer Cachexia Impairs Skeletal Muscle Mitochondrial Function and Content - Neyroud, Daria (J Muscle Res Cell Motil, 2019)
INTRODUCTION. The present study aimed to determine the impact of colon 26 adenocarcinoma (C26)-induced cancer cachexia on skeletal muscle mitochondrial respiration and content. METHODS. Twelve male CD2F1 mice were injected with C26-cells (tumor bearing (TB) group), whereas 12 age-matched mice received PBS vehicle injection (non-tumor bearing (N-TB) group). Mitochondrial respiration was studied in saponin-permeabilized soleus myofibers. RESULTS. TB mice showed lower body weight (~ 20%) as well as lower soleus, gastrocnemius-plantaris complex and tibialis anterior masses versus N-TB mice (p<0.05). Soleus maximal state III mitochondrial respiration was 20% lower (10 mM glutamate, 5 mM malate, 5 mM adenosine diphosphate; p<0.05) and acceptor control ratio (state III/state II) was 15% lower in the TB vs. N-TB (p<0.05), with the latter suggesting uncoupling. Lower VDAC protein content suggested reduced mitochondrial content in TB versus N-TB (p<0.05). DISCUSSION. Skeletal muscle in C26-induced cancer cachexia exhibits reductions in: maximal mitochondrial respiration capacity, mitochondrial coupling and mitochondrial content.